Experimental model of atrophic rhinitis in gnotobiotic pigs. - Ackermann, M R (1991)
To study the pathogenesis of atrophic rhinitis, gnotobiotic pigs (n = 6) were inoculated intranasally with a sterile sonicate of a toxigenic strain of Bordetella bronchiseptica (0.16 mg of protein per ml) at 5 days of age, and they were then inoculated intranasally with 1 ml (5,250 CFU/ml) of a live, toxigenic strain of Pasteurella multocida at 7 days of age. Pigs were necropsied at 2, 5, 9, 14, 21, and 28 days postinoculation; those pigs necropsied after 5 days had developed turbinate atrophy. Other gnotobiotic pigs received the following inoculation protocols: (i) a sterile sonicate of a nontoxigenic strain of B. bronchiseptica (0.2 mg of protein per ml), followed by toxigenic P. multocida (n = 4); (ii) toxigenic P. multocida alone (n = 7); (iii) diluent (sterile tryptose broth) (n = 2); (iv) the sterile sonicate of toxigenic B. bronchiseptica alone (n = 2); or (v) the sterile sonicate of a nontoxigenic strain of B. bronchiseptica alone (n = 2). Turbinate atrophy did not occur in the latter groups except for one pig inoculated with only toxigenic P. multocida. These studies show that turbinate atrophy occurs in pigs given the toxigenic B. bronchiseptica sonicate and then given live, toxigenic P. multocida. This experimental regimen is a useful model for (i) studying the pathogenesis of atrophic rhinitis and (ii) testing vaccine strategies.